Landscape of natural killer cell activity in head and neck squamous cell carcinoma. Issue 2 (21st December 2020) - Charap, Andrew J; Enokida, Tomohiro; Brody, Rachel; Sfakianos, John; Miles, Brett; Bhardwaj, Nina; Horowitz, Amir
Abstract : Head and neck squamous cell carcinoma (HNSCC) encompasses a set of cancers arising from the epithelia of the upper aerodigestive tract, accounting for a significant burden of disease worldwide due to the disease's mortality, morbidity, and predilection for recurrence. Prognosis of HNSCC in the recurrent and/or metastatic (R/M-HNSCC) setting is especially poor and effective treatment options increasingly rely on modulating T-cell antitumor responses. Still, immunotherapy response rates are generally low, prompting the exploration of novel strategies that incorporate other effector cells within the tumor microenvironment. Within the last decade, important advances have been made leveraging the powerful innate antitumor function of natural killer (NK) cells to treat solid tumors, including head and neck squamous cell carcinoma. NK cells are hybrid innate-adaptive effector cells capable of directly eliminating tumor cells in addition to initiating adaptive antitumor immune responses. In the setting of HNSCC, NK cells are important for tumor surveillance and control, and NK cell infiltration has repeatedly been associated with a favorable prognosis. Yet, HNSCC-infiltrating NK cells are susceptible to an array of immune evasion strategies employed by tumors that must be overcome to fully realize the antitumor potential of NK cells. We believe that a conceptual framework informed by the basic biological understanding of the mechanisms underlying NK cell activation can improve treatment of HNSCC, in part by selecting for patients most likely to respond to NK cell-based immunotherapy. Herein, we review the activity of NK cells in HNSCC, paying special attention to the role of environmental and genetic determinants of NK cell antitumor function. Moreover, we explore the evidence that NK cells are a crucial determinant of the efficacy of both established and emerging treatments for HNSCC.